when you have an exponent to an exponent. You multiply the exponent.
(-x^2)
= (-1 * x^2)^3
= (-1)^3 * x^6
= -x^6
2007-06-28 12:03:25
·
answer #1
·
answered by 7
·
0⤊
0⤋
To simplify this, simply you have to multiply the powers as follows:
(-X)^(2*3) = -X^6
2007-06-28 12:16:12
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
(-x^2)^3 = -x^2 * -x^2 * -x^2 = -x^6
Remember when the outer exponent is odd, the answer's sign is the same as the inside.
When the outer exponent is even, the answer's sign is always positive.
2007-06-28 12:05:50
·
answer #3
·
answered by kousuke51 2
·
0⤊
0⤋
Remember these rules for exponents:
(ab)^c = (a^b)(a^c)
(a^b)^c = a^(bc)
So here we have:
(-x^2)^3
(-1 * x^2)^3
(-1)^3 (x^2)^3
- x^6
2007-06-28 12:05:12
·
answer #4
·
answered by Anonymous
·
0⤊
1⤋
oh thats easy just multiply the exponents together
answer= -x^6
2007-06-28 12:23:07
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
easy just multiply the exponents together
answer: -x^6
2007-06-28 12:02:13
·
answer #6
·
answered by superman 4
·
0⤊
0⤋
[(-1) x² ] ³ = (-1)³. x^(6) = - (x^6)
2007-07-02 07:10:49
·
answer #7
·
answered by Como 7
·
0⤊
0⤋
(-x²)³ = -x^6
>::<
2007-06-28 12:02:47
·
answer #8
·
answered by aeiou 7
·
0⤊
0⤋
When you take a power to a power, you multiply them.
-x^6
2007-06-28 12:08:52
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋